The endoplasmic reticulum stress sensor IRE1α modulates macrophage metabolic function during Brucella abortus infection - Guimarães, Erika S.; Gomes, Marco Túlio R.; Sanches, Rodrigo C. O.; Matteucci, Kely Catarine; Marinho, Fábio V.; Oliveira, Sergio C. (Frontiers in Immunology, 2023)
Endoplasmic reticulum (ER) stress plays a major role in several inflammatory disorders. ER stress induces the unfolded protein response (UPR), a conserved response broadly associated with innate immunity and cell metabolic function in various scenarios. Brucella abortus, an intracellular pathogen, triggers the UPR via Stimulator of interferon genes (STING), an important regulator of macrophage metabolism during B. abortus infection. However, whether ER stress pathways underlie macrophage metabolic function during B. abortus infection remains to be elucidated. Here, we showed that the UPR sensor inositol-requiring enzyme 1α (IRE1α) is as an important component regulating macrophage immunometabolic function. In B. abortus infection, IRE1α supports the macrophage inflammatory profile, favoring M1-like macrophages. IRE1α drives the macrophage metabolic reprogramming in infected macrophages, contributing to the reduced oxidative phosphorylation and increased glycolysis. This metabolic reprogramming is probably associated with the IRE1α-dependent expression and stabilization of hypoxia-inducible factor-1 alpha (HIF-1α), an important molecule involved in cell metabolism that sustains the inflammatory profile in B. abortus-infected macrophages. Accordingly, we demonstrated that IRE1α favors the generation of mitochondrial reactive oxygen species (mROS) which has been described as an HIF-1α stabilizing factor. Furthermore, in infected macrophages, IRE1α drives the production of nitric oxide and the release of IL-1β. Collectively, these data unravel a key mechanism linking the UPR and the immunometabolic regulation of macrophages in Brucella infection and highlight IRE1α as a central pathway regulating macrophage metabolic function during infectious diseases.